Kewenangan Mahkamah Konstitusi Memutus Perselisihan Hasil Pemilu Sebagai Bentuk Judicialization 0f Politics - Satrio, Abdurrachman (Jurnal Konstitusi, 2015)
Judicialization of politics are the phenomenon which usually happen in a democratic constitutional state, which cause power movement to resolve problems which related to public policy making and political nature, from the political institution to judicial institution. In Indonesia this phenomenon arise in the authority of the Constitutional Court, especially in the authority of the Constitutional Court when they adjudicate electoral result dispute, whichs so far, most widely submitted cases to the Constitutional Court. But, as a independent and impartial judicial institution the Constitutional Court must restrict to adjudicate the political cases such as electoral result dispute so that this institution would not be politicking object of another branch of government, however judicialization of politics phenomenon is something that Constitutional Court would not avoid, so that this article will examine how important the Constitutional Court to priority judicial restraint principle in order to adjudicate electoral result dispute, so that Constitutional Court would not be politicking object of another branch of government.